Bioconcentration, phytotoxicity and health risk of microcystins in crops: research progress - Qing LUO; Guanxiang YUAN; Guihua LIU (Editorial Office of Chinese Journal of Public Health, 2023)
Microcystins (MCs), being among the most concerned cyanobacterial toxins and with acute hepatotoxic effects, can induce liver damage and even lead to liver cancer after long-term intake. Addition to existing in contaminated water and aquatic products, MCs can also be accumulated in crops via polluted irrigation water, which could increase the health risk of human. In this paper, we systematically reviewed the enrichment characteristics of MCs in different crops and their toxicities to those crops. The potential health risks from MCs residues in edible parts of crops were also discussed.